2017
DOI: 10.5830/cvja-2016-083
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and radiological findings of pulmonary embolism in HIV-positive patients referred for computed tomography pulmonary angiography in the Western Cape of South Africa

Abstract: SummaryAim:To provide imaging data and report associations between human immunodeficiency virus (HIV), tuberculosis (TB) and pulmonary embolism (PE) in a South African population that underwent computed tomography pulmonary angiography (CTPA) for suspected PE.Methods:A validated Qanadli severity scoring system for PE was used for 164 CTPA scans, and parenchymal, pleural and cardiovascular complications were reported. Serological confirmation of HIV testing and microbiological confirmation of TB were recorded.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
0
10
3
Order By: Relevance
“…Pleural effusion was present in 57% of the PE-positive cases in this study. This is higher than the 45% in the study on HIVinfected patients by Ramlakhan et al 11 , as well as higher than the 25.8% in the study by Sharma et al 14 studies carried out on both HIV-infected and -negative populations. 7,11,14 These findings are traditionally thought to be due to PE.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Pleural effusion was present in 57% of the PE-positive cases in this study. This is higher than the 45% in the study on HIVinfected patients by Ramlakhan et al 11 , as well as higher than the 25.8% in the study by Sharma et al 14 studies carried out on both HIV-infected and -negative populations. 7,11,14 These findings are traditionally thought to be due to PE.…”
Section: Discussioncontrasting
confidence: 53%
“…5,6,7,9 This is in keeping with other literature on HIV-infected patients where the mean ages for PE were younger than the general population, ranging from 40 to 45 years. 2,3,10,11,12 Presenting symptoms in this study were typical of that described in the Prospective Investigation of Pulmonary Embolism Diagnosis (PIOPED II) trial, including shortness of breath, syncope, chest pain and haemoptysis -all of which are non-specific. 13 The CTPA prevalence of PE in an HIV-infected study population in this study was found to be 35%.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…While chronic obstructive pulmonary disease and pulmonary hypertension secondary to left-sided heart failure are seen in all settings, chronic fibrocavitary TB is a frequent underlying cause in Africa [42]. In addition, HIV, schistosomiasis, and pulmonary embolism can lead to chronic pulmonary hypertension eventually resulting in cor pulmonale [43,44]. Moreover, patients with HIV may suffer from HIV-associated pulmonary artery hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first case of PE associated with malaria was documented in Kampala (Musoke et al, 2014). And the association of PE with HIV/AIDS infection and with tuberculosis have been described (Ekukwe, 2014;Ramlakhan et al, 2017;Park et al, 2017;Gupta et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%